2003
DOI: 10.1046/j.1365-2222.2003.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of alcohol consumption with total serum immunoglobulin E levels and allergic sensitization in an adult population‐based survey

Abstract: Alcohol consumption above a certain threshold is associated with an increase in total serum IgE levels. Alcohol consumption may also be associated with an increased prevalence of pollen sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
117
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 38 publications
9
117
0
1
Order By: Relevance
“…In other studies, alcohol beverages consumption has been associated with increased risk for asthma and hay fever symptoms, allergic sensitization and serum IgE (45)(46)(47). The aMED score, used in the present study, considers total ethanol intake, irrespective of the different alcoholic beverages.…”
Section: Discussionmentioning
confidence: 98%
“…In other studies, alcohol beverages consumption has been associated with increased risk for asthma and hay fever symptoms, allergic sensitization and serum IgE (45)(46)(47). The aMED score, used in the present study, considers total ethanol intake, irrespective of the different alcoholic beverages.…”
Section: Discussionmentioning
confidence: 98%
“…A detailed description of the study has been reported elsewhere [35]. Briefly, it entails a cross-sectional survey of an age-stratified random sample of the adult population (≥18 years) from the municipality of A-Estrada (Spain).…”
Section: Methodsmentioning
confidence: 99%
“…The study profile is represented in figure 1. There were no differences in sex, age or habitat (rural/urban) between individuals who participated in the study and those who did not [35]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our evidence that EtOH polarizes the immune response toward Th2-driven immunity, deregulating the Th I response may explain the immunological impairments observed in alcohol abusers (1,3,(29)(30).…”
Section: Discussionmentioning
confidence: 76%